دور التنسيق النمطي للبناء المصنع في سرعة انجاز الوحدات السكنية - محيي هلال العقيلي ميسون (Journal of Engineering and Sustainable Development, 2009)
Providing appropriate housing for everyone is an important prerequisite for the progress of countries. it is, moreover, an indication of stability in man’s life. Thus, the present research tackles the precast typological coordination and how to use it in satisfying the increasing need for housing in a country like Iraq where there has been an accumulative housing shortage due to the current and accumulative housing needs, and the deteriorated condition of the existing buildings. this is proposed to be done by selecting a typical standardized plan that can be easily applied and implemented to reduce the time factor.